Microstructure and Mechanical Properties of TiC Nanoparticle-Reinforced Iron-Matrix Composites - Kim, J.M.; Park, J.S.; Yun, H.S. (Проблемы прочности, 2014)
Uniformly distributed TiC nanoparticle-reinforced iron-based composites were successfully fabricated by planetary milling in argon and subsequent hot pressing procedures. Nearly full density composite specimens could be obtained via 6-hour milling and hot pressing at 1100° C under 50 MPa. Spherical TiC particles and fine fibrous Fe₃C phases were observed to form the iron-matrix composites and subjected to comparative analysis. Microstructural analysis results show that theaverage diameter of TiC particles and the length of Fe₃C phases tend to decrease with an increase in a TiC volume content. The compression yield strength of hot-pressed composites increased in proportion to the TiC content, resulting in 1.3 GPa for 7.5% TiC. The relationship between the microstructural characteristics and the yield strength of TiC-reinforced composites was also investigated. Based on the Orowan strengthening mechanism, a higher strength is observed for a high TiC content, mainly due to reduced distance between reinforcing TiC nanoparticles.